Pengembangan Keprofesian Berkelanjutan Melalui Pendalaman Materi Esensial Bagi Guru MGMP Fisika Madrasah Aliyah Kabupaten Jember - Supeno; Trapsilo Prihandono; Albertus Djoko Lesmono; Enike Kusumawati; Mamik Islami Nurhidayati (Jurnal Pengabdian UntukMu NegeRI, 2022)
Physics teachers must master the structure, concepts, scientific mindset and develop subject matter to provide broad and deep knowledge for students. Professional teachers must develop professionalism continuously through lifelong learning, one of which is to explore the essential material to increase mastery of the content of the subject matter. Physics teachers who are members of the Madrasah Aliyah Physics Teacher Consultation forum throughout Jember Regency have carried out continuous professional development, especially mastering essential physics materials. The activity implementation team, FKIP lecturers at the University of Jember, and core teachers discussed crucial physics materials. The results of this activity show that physics teachers can master the essential physics subject matter, are categorized as complex, and often lead to misconceptions. Teachers are also able to plan and carry out physics practicum. Teachers can use mastery of physics subject matter to design physics teaching materials and physics assessments to improve the quality of physics learning.